Revisit once more the sensory storage account of visual working memory. Issue 5 (13th September 2020) - Xu, Yaoda
ABSTRACT: Recent work has highlighted the role of early visual areas in visual working memory (VWM) storage and put forward a sensory storage account of VWM. Using a distractor interference paradigm, however, we previoulsy showed that the contribution of early visual areas to VWM storage may not be essential. Instead, higher cortical regions such as the posterior parietal cortex may play a more significant role in VWM storage. This is consistent with reviews of other available behavioural, neuroimaging and neurophysiology evidence. Recently, a number of studies brought forward new evidence regarding this debate. Here I review these new pieces of evidence in detail and show that there is still no strong and definitive evidence supporting an essential role of the early visual areas in VWM storage. Instead, converging evidence suggests that early visual areas may contribute to the decision stage of a VWM task by facilitating target and probe comparison. Apart from further clarifying this debate, it is also important to emphasize that whether or not VWM storage uses a sensory code depends on how it is defined, and that behavioural interactions between VWM and perception tasks do not necessarily support the involvement of sensory regions in VWM storage.